2017
DOI: 10.1371/journal.pone.0178372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulmonary vascular permeability index PVPI and global ejection fraction GEF derived from jugular and femoral indicator injection using the PiCCO-2 device: A prospective observational study

Abstract: BackgroundTranspulmonary thermodilution (TPTD) is used to derive cardiac output CO, global end-diastolic volume GEDV and extravascular lung water EVLW. To facilitate interpretation of these data, several ratios have been developed, including pulmonary vascular permeability index (defined as EVLW/(0.25*GEDV)) and global ejection fraction ((4*stroke volume)/GEDV). PVPI and GEF have been associated to the aetiology of pulmonary oedema and systolic cardiac function, respectively. Several studies demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…By contrast, our findings of a substantial overestimation of GEDVI by the EV-1000 in case of femoral indicator injection are in line with the only one case report addressing this issue 13 . Both studies demonstrate that the www.nature.com/scientificreports/ slightly different algorithm of the EV-1000 to derive raw GEDV from the thermodilution curve is not capable to correct for femoral indicator injection resulting in an increase in the mean transit time due to the additional volume of the inferior vena cava 15,19 . In case of femoral indicator injection the two devices are not interchangeable even in case of use of unindexed GEDV due to the absence of a correction in the EV-1000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, our findings of a substantial overestimation of GEDVI by the EV-1000 in case of femoral indicator injection are in line with the only one case report addressing this issue 13 . Both studies demonstrate that the www.nature.com/scientificreports/ slightly different algorithm of the EV-1000 to derive raw GEDV from the thermodilution curve is not capable to correct for femoral indicator injection resulting in an increase in the mean transit time due to the additional volume of the inferior vena cava 15,19 . In case of femoral indicator injection the two devices are not interchangeable even in case of use of unindexed GEDV due to the absence of a correction in the EV-1000.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have suggested a correction formula for GEDVI based on data derived from femoral TPTD and biometric information 12 , 13 . Consequently, the manufacturer of the PiCCO device introduced a new software requiring information about the CVC site, and correction for femoral indicator injection can be assumed 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Since this mathematical correction maybe cumbersome in clinical routine, GEF can be used instead of CFI. At least two studies suggest that GEF is appropriately corrected for femoral indicator injection by the most recent PiCCO algorithm [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients had to be equipped with PiCCO device and with both jugular and femoral catheter. The indication for PiCCO monitoring was made independently from the study by the ICU physician in charge None of the patients had been included in one of the previous studies or databases comparing TPTD-parameters derived from jugular to femoral indicator injection [ 14 , 15 , 17 19 ]. After fulfilling above-mentioned criteria no patient was excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation